The Role of Taxes as Automatic Destabilizers in New Keynesian Economics - Claus Thustrup Hansen; Henrik Jacobsen Kleven (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper analyses the effects of taxation in New Keynesian economics. The results show that taxes contribute to price and wage stickiness and, moreover, that the resulting fluctuations in welfare are magnified by the presence of taxes. These results are at odds with the old Keynesian idea of automatic stabilizers.
Keywords: E32; E62; 330; New Keynesian economics; taxation; automatic stabilizers